1977
DOI: 10.1161/01.cir.56.5.737
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment and interruption of atrial flutter with atrial pacing: studies in man following open heart surgery.

Abstract: To examine the question of why the pacing rate and duration of atrial pacing are crucial factors in the successful interruption of atrial flutter, studies were performed on 30 patients in the period following open heart surgery. In each patient the diagnosis of atrial flutter was made using a pair of wire electrodes placed on the right atrial epicardium at the time of operation and brought out through the anterior chest wall. The same electrodes were used for atrial pacing. Pacing faster than the spontaneous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0
6

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 434 publications
(118 citation statements)
references
References 30 publications
0
112
0
6
Order By: Relevance
“…After mapping atrial activation with endocardial and esophageal recordings, Puech et al 3 concluded that the flutter cycle in the human heart involved activation of the whole right atrium. Stimulation studies by Waldo et al 4 revealed that in postoperative AFl the arrhythmia was based on a reentry mechanism involving a large atrial area. They demonstrated the presence of an excitable gap that allowed the speeding up of the flutter rate during atrial pacing and termination of the arrhythmia by pacing.…”
Section: Historymentioning
confidence: 99%
“…After mapping atrial activation with endocardial and esophageal recordings, Puech et al 3 concluded that the flutter cycle in the human heart involved activation of the whole right atrium. Stimulation studies by Waldo et al 4 revealed that in postoperative AFl the arrhythmia was based on a reentry mechanism involving a large atrial area. They demonstrated the presence of an excitable gap that allowed the speeding up of the flutter rate during atrial pacing and termination of the arrhythmia by pacing.…”
Section: Historymentioning
confidence: 99%
“…First, only atrial fusion was encountered. In the four patients with AV bypass pathways capable of retrograde conduction figure 2 at the termination of overdrive pacing of the paroxysmal atrial tachvcardia from the distal pair of electrodesfrom the high right atrial electrode catheter at the same cvcle length as infigure 6. This episode was recorded just before that shown in figure 6.…”
mentioning
confidence: 94%
“…70,71 Transthoracic direct-current cardioversion, under short-lasting sedation, is the quickest and most effective method to recover sinus rhythm in patients with flutter, with a lower energy delivery and higher success rate than in AF. 72,73 In 50-80 % of cases flutter interruption can be achieved by atrial pacing above the flutter rate through a transvenous catheter, through epicardial electrodes placed during cardiac surgery 8 or by programming fast atrial rates in patients with atrial or dual-chamber pacemakers. 74 Pacing runs of 20-30 s are started at a rate 10 bpm higher than flutter, increasing in 10 bpm steps up to 400 bpm or until flutter is interrupted and sinus (or paced) atrial rhythm is established (see Figure 6).…”
Section: 69mentioning
confidence: 99%
“…140 This high incidence is related to inflammatory changes in the atrial myocardium, 141 not unlike the experimental pericarditis animal models, 142 and it may be prevented by anti-inflammatory corticosteroid treatment. 143,144 AF is the most commonly reported arrhythmia but flutter can also occur in this setting, 8,35,78 although its frequency in relation to AF is not clear. There are very few data on the long-term follow-up of this postoperative flutter, but the incidence of AF in such cases is reported to be around 30 %.…”
Section: Postoperative Atrial Fluttermentioning
confidence: 99%